The Opportunity Cost of Capital - Ayman Chit PhD; Ahmad Chit CA; Manny Papadimitropoulos PhD; Murray Krahn MD; Jayson Parker PhD; Paul Grootendorst PhD (SAGE Publishing, 2015)
The opportunity cost of the capital invested in pharmaceutical research and development (R&D) to bring a new drug to market makes up as much as half the total cost. However, the literature on the cost of pharmaceutical R&D is mixed on how, exactly, one should calculate this "hidden" cost. Some authors attempt to adopt models from the field of finance, whereas other prominent authors dismiss this practice as biased, arguing that it artificially inflates the R&D cost to justify higher prices for pharmaceuticals. In this article, we examine the arguments made by both sides of the debate and then explain the cost of capital concept and describe in detail how this value is calculated. Given the significant contribution of the cost of capital to the overall cost of new drug R&D, a clear understanding of the concept is critical for policy makers, investors, and those involved directly in the R&D.